Gestational weight gain among Malay women with high risk pregnancy in Kelantan tertiary hospitals : a mixed method study - Fathil, Noor Farhana Mohd (2018)
Gestational weight gain is an important predictor of short and long-term pregnancy outcomes for both mother and her offspring. Little information is available regarding modifiable factors contributing to suboptimal weight gain among Malay women. The aim of this study was to determine the proportion and factors associated with gestational weight gain among Malay women with high risk pregnancy; and to explore women’s perceptions and experience in relation to excess weight gain. A convergence parallel mixed method study comprising of quantitative and qualitative study was conducted among Malay women with high risk pregnancy in third trimester who attended antenatal clinic in tertiary hospitals, Kelantan. There were 399 Malay pregnant women who met the study criteria for the survey. Systematic sampling was applied. A subsample of 23 women with excessive weight gain were interviewed individually representing different range of pre-pregnancy body mass index (BMI), gravidity, education level and employment status. Multinomial logistic regression was used to analyse the association between gestational weight gain and contributing factors. Thematic analysis was used to identify recurring themes. Initial data analysis of quantitative and qualitative were done separately, then both data derived were converged and triangulated to address the research question. The proportion of excessive, adequate and inadequate gestational weight gain was 39.8% (95% CI; 35.0, 44.8), 34.8% (95% CI; 30.2, 39.7) and 25.4% (95% CI; 21.1, 29.9), respectively. Pre-pregnancy BMI overweight and obese (AOR 1.75; 95% CI: 1.07, 2.86; p-value =0.026) was the only factor significantly associated with excessive gestational weight gain. There were three major themes emerged from the interviews (23 IDIs) which were; prioritised the needs of their unborn baby; negative feelings about pregnancy weight gain and belief regarding main contributors to excess weight gain. Pre-pregnancy BMI was a strong predictor of excessive GWG. It was related to the cultural practices, weight gain from previous pregnancy and lifestyle issues as identified in the qualitative study. Our findings can serve as future intervention messages and strategies to provide best antenatal care in avoiding excessive weight gain.